2010
DOI: 10.1016/j.humpath.2009.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity of HER-2 gene amplification and protein overexpression in breast cancer

Abstract: We report a case of a patient with invasive breast carcinoma which demonstrated HER-2 gene amplification on core biopsy, who relapsed while on adjuvant Trastuzumab therapy following her mastectomy and ultimately died 15 months after diagnosis. Surprisingly, analysis of multiple metastases harvested at rapid autopsy demonstrated no evidence of HER-2 gene amplification. Retrospective examination of the carcinoma in the patient’s mastectomy specimen revealed only focal HER-2 amplification within the tumor, locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 13 publications
(12 reference statements)
0
27
0
Order By: Relevance
“…Striebel et al 22 supported this idea by showing that the HER2 status of 10 (59%) of 17 breast cancers with equivocal HER2 amplification on core biopsy changed in the resection specimens, and they stressed the heterogeneity of gene amplification and protein expression in breast cancers with low HER2 gene copy numbers. Recently, Wu et al 38 reported a case of intratumoral heterogeneity of HER2 gene amplification, which showed HER2 gene amplification on core biopsy but not in metastases. In that case, only focal HER2 amplification was found in the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Striebel et al 22 supported this idea by showing that the HER2 status of 10 (59%) of 17 breast cancers with equivocal HER2 amplification on core biopsy changed in the resection specimens, and they stressed the heterogeneity of gene amplification and protein expression in breast cancers with low HER2 gene copy numbers. Recently, Wu et al 38 reported a case of intratumoral heterogeneity of HER2 gene amplification, which showed HER2 gene amplification on core biopsy but not in metastases. In that case, only focal HER2 amplification was found in the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35] Moreover, aneuploidy of Chr17 and alterations of Cep17 represent indicators of genetic instability, which contributes to the progression of breast cancer through accumulation of genomic aberrations; discovery of recurrent DNA alterations 32 and of the genes that are deregulated by these aberrations will help to understand the mechanisms of breast cancer biology and lead to improvements in its diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in HER-2 status found in core biopsy, mastectomy and metastasis specimens, and the heterogeneous HER-2 protein expression (HER-2 phenotypic heterogeneity, PH) found in a primary tumour from mastectomy specimen in the case described by Wu et al, 6 from this point of view, are paradigmatic.…”
Section: Her-2 Intratumoral Heterogeneitymentioning
confidence: 99%
“…Cases whose results are at or near the cutoff point and that, therefore, 'should be interpreted with caution', 3,6 can become a real interpretative nightmare. Furtheremore, we believe that also HER-2 PH should be taken into due consideration when reporting a HER-2 characterization test.…”
Section: Her-2 Intratumoral Heterogeneitymentioning
confidence: 99%